In process monitoring of cutting temperature during the drilling of FRP laminate. (15th May 2017) - Sorrentino, L.; Turchetta, S.; Bellini, C.
Abstract: Drilling is the most important machining operation applicable to polymeric composite materials since it is essential for mechanical coupling of parts. Drilling process provokes several issues, including localized thermal shock, caused by the presence of abrasive and extremely hard fibres and the low thermal conductivity of composite, which restricts the heat dissipation. Such dangerous issue can be evaluated by examining the process temperature, whose value depends on cutting parameters. Therefore, monitoring of process temperature is indispensable to obtain useful information for machining optimization. In this work the influence of cutting parameters was analysed, measuring the temperature during drilling on tool and in the laminate for both CFRP and GFRP. Temperature trends as a function of cutting speed and feed rate were obtained and dangerous values of cutting parameters were identified. Finally, a preliminary numerical model was developed to simulate the temperature rising in the material during drilling.